Melanoma cutâneo: aspectos histológicos e clínicos dos casos diagnosticados no Hospital das Clínicas da Universidade Federal de Minas Gerais no período de 1995 a 2017 - Pedro Lobo Alcantara Neves (2018)
Introduction: Although not being the most prevalent skin neoplasm, cutaneous melanomais the most lethal, accounting for about 75% of skin cancer deaths. Its incidence has been increasing worldwide, coming to the 5th position in the United States. In Brazil, the epidemiological and histological characteristics of the lesions are restricted to those reported in small series of cases, even in view of the increased importance of the neoplasia. Objective: To describe the clinical and histopathological aspects of cutaneous melanomas diagnosed in patients attended at Hospital das Clínicas, Federal University of Minas Gerais. Methods: Were selected cases of cutaneous melanoma diagnosed at the Hospital das Clínicas of the Federal University of Minas Gerais between 1995 and 2017. These cases were evaluated for clinical data (age at diagnosis, lesion location and gender of patients) and histological variables (histological subtype, thickness, invasion level, ulceration, regression, microsatellitosis, vascular invasion, neurotropism, tumor-infiltrating lymphocytes, surgical margins and mitotic index). Slides from 40 of these cases were scanned and sent to three pathologists with more than 15 years of experience in surgical pathology to assess interobserver agreement for the following parameters: histological subtype, thickness, invasion level, ulceration, regression, microsatellite, vascular invasion, neurotropism and tumor-infiltrating lymphocytes. To evaluate the level of agreement, the Kappa test wasused. Results: Were selected 223 cases of cutaneous melanoma,in situ and invasive. Thepatients' ages ranged from 18 to 88 years, with an average of 60 years. More thanhalf of the diagnoses occurred in people over 59 years-old (120 cases, 53.8%). The gender distribution was not statistically different: 122 (54.7%) in women and 101 (45.3%) in men. The predominant location was the head and neck region (95 cases, 42.6%), followed by the trunk (54 cases, 24.2%) and extremities (72 cases, 32.3%). Intwocases (0.9%) the location was not specified. The predominant histological subtype was superficial spreading (130cases,58.3%),followed by lentigo maligna/lentigomalignamelanoma(55cases,24.7%),acrallentiginous(20cases, 9.0%) and nodular (18 cases, 8.1%). The interobserver agreement levels according to the Kappa test were good or very good, except for the parametertumor-infiltratinglymphocytes, which was fair or poor. Conclusion: Cutaneous melanoma predominated in the older age group (average = 60 year). There was no significant difference between the patients' gender. The most prevalent location was the head and neck region. The most common histological subtype, including in situ and invasive melanomas, was superficial spreading, followed by lentigo maligna / lentigo maligna melanoma. The interobserver agreement level was good or very good for the most histological parameters. The histopathological diagnosis of melanomas can be performed safely and reproductively by non-specialist pathologists.